Faktor-Faktor yang Mempengaruhi Keputusan Generasi Z dalam Berinvestasi (Studi pada Mahasiswa Universitas Kh. A Wahab Hasbullah) - Lailatus Sa’adah; Famung Gangga; Tata Mifthakul Janah; Binti Ayu Fadhilah (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study analyzes the factors influencing Generation Z's investment decisions. Investment is a form of financial preparation for the future. According to the KSEI report for 2022, investors under 30 years old account for 60.02%, indicating that Generation Z is becoming increasingly aware of the importance of investing. This research employs a qualitative descriptive approach using survey methods, with data collection through interviews. The data for this study were gathered from six university students at KH Wahab Hasbullah University. The purpose of this research is to identify the factors influencing Generation Z's investment decisions, such as investment knowledge, investment motivation, technological advancement, investment interest, lifestyle, ease of using investment applications, and investment decisions. Technological advancement refers to developments in line with scientific progress, resulting in innovations aimed at simplifying daily life. Investment can attract Generation Z students through technology and digital platforms to encourage investment activities. Investment decisions refer to the planning and decision-making process related to short-term or long-term fund expenditures and the return of those funds. Investment decisions serve as the initial step in determining the amount of assets required by the company as a whole, making investment decisions a critical aspect.